Gardner's guide to writing and producing television - LaDuke, Dee (GGC Pub., 2007)
Provides practical guidelines for writing a script, selling a pilot to networks, and producing episodes. A hands-on manual to working with writers, producers, directors, and actors, this book also provides industry interviews with experts working in television and provides solutions to common pitfalls and pratfalls with the business.